Analisis Kinerja Prosesor terhadap Proses Overclocking dan Downclocking - Azhar Azhar; Firdaus H (Universitas Muhammadiyah Makassar, 2019)
The rapid development of technology causes hardware technology is also experiencing rapid pekembangan, so that the existing hardware to be fast using, Computers is an electronic device capable of performing several tasks as follows, receive input, process the input earlier in accordance with the program, save the commands and the results of processing. The purpose of this study is to show how much influence is given by overclocking and downclocking process to processor performance, to know the effect on the working temperature generated and the power used from the process. This research method is data analysis with tools that have been prepared. The result of this research is by application of benchmark of synthesis, graph of which shows that the higher the value hence the better its performance, except in Super Pi application which uses second time unit (s) where less time required in test indicate optimal processor performance, to overcome from the need for high computing and so as not to rush to upgrade hardware and also to save more cost in hardware upgrade. The conclusion is the frequency of downcloking generated by 1000 MHz, standard frequency 3000 MHz, Overclocking frequency of 3750 MHz, unstable system, with the overclock system will be unstable until lag / hang unstable system occurs at frequencies above 3.75 GHz.